Tinjauan Fiqh Mu'amalah terhadap Jual Beli Bibit Udang (Benur) Sistem Sampling di Desa Meluntur Glagah Kabupaten Lamongan - Moh. Miftahun Ni’am; Ach. Mus’if (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
This thesis departs from the background of the buying and selling of shrimp seeds in Meluntur Village which does not count the objects of sale and purchase in counting units, but rather in scoop measurements which are then used as sampling for the next measurement. Formulation of the problem regarding the practice of buying and selling shrimp seeds (Benur) using a sampling system in Meluntur Village and reviewing the mu'amalah fiqh regarding the legal practice of buying and selling. The aim of the research and the benefits of the research are to determine the practice of buying and selling shrimp seeds using a sampling system in Meluntur Village and analysis of the legal review of mu'amalah fiqh. The research method in this thesis uses a qualitative method with a descriptive qualitative approach, the research subjects are sellers, namely shrimp seed pond farmers and buyers, with the research object being shrimp seeds. The data sources for this research utilize primary and secondary data sources. Data collection techniques using observation, interviews and documentation. Data analysis method using data reduction and data presentation and drawing conclusions.